2020
DOI: 10.3847/1538-4357/abb08a
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Primary X-Ray Emission and Possible Starburst Component in the Polarized NLS1 Mrk 1239

Abstract: X-ray observations of the unique NLS1 galaxy Mrk 1239 spanning 18 yr are presented. Data from XMM-Newton, Suzaku, Swift, and NuSTAR are combined to obtain a broadband, multi-epoch view of the source. There is spectral variability in the 3–10 keV band over the 18 yr. An analysis of the NuSTAR and Suzaku lightcurves also suggests rapid variability in the 3–10  keV band, which is consistent with the NLS1 definition of the source. However, no variability is seen below 3 keV on any timescale. Two distinct physica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…Consistent with this its star formation rate was estimated to be 3.47 M yr −1 based on SED modelling (Gruppioni et al 2016). Buhariwalla et al (2020) modelled the X-ray spectrum of J0952-0136 with alternative models and found that the < 3 keV emission cannot be modelled without a starburst component, whose extent they estimate to be less than 400 pc from the nucleus. This is interesting since the other star formation proxies do not predict starburst level star formation.…”
Section: J0952-0136mentioning
confidence: 76%
“…Consistent with this its star formation rate was estimated to be 3.47 M yr −1 based on SED modelling (Gruppioni et al 2016). Buhariwalla et al (2020) modelled the X-ray spectrum of J0952-0136 with alternative models and found that the < 3 keV emission cannot be modelled without a starburst component, whose extent they estimate to be less than 400 pc from the nucleus. This is interesting since the other star formation proxies do not predict starburst level star formation.…”
Section: J0952-0136mentioning
confidence: 76%
“…. Buhariwalla et al (2020) found an Eddington ratio of Edd = 1 − 1.5. Yao et al (2018) applied a correction factor to the 5100 of Mrk 1239 and obtained Edd = 1.12.…”
Section: Ultra-soft X-ray Continuum Emissionmentioning
confidence: 99%
“…A super-solar Ne abundance of Ne = 4.9 +1.2 −1.3 is needed. Buhariwalla et al (2020) suggested that these hot plasma components may be associated with the star-burst region in the host galaxy of Mrk 1239. This component has been often found in the soft X-ray emission of many obscured sources (e.g.…”
Section: Hot Diffuse Plasma With Super-solar Ne Abundancesmentioning
confidence: 99%
See 2 more Smart Citations